Indentation damage evaluation on metal-coated thin-films stacked structure - Yeo, Alfred (2015)
A micro-indentation system integrated with an acoustic emission (AE) sensor is used as a damage test method for crack detection of the specimen during the indentation loading–unloading cycle. The specimens investigated are the Si die, and various stacked structures of metallization (Al or Cu) deposited over the dielectric layers (SiO2 or Si3N4) on the Si substrate. The 1st AE event detected during the loading stage corresponded to the ‘pop-in’ observation in the force–displacement curve, which was related to the brittle cracking in the dielectric or Si substrate. However, during unloading, a 2nd AE event was detected, but no “pop-out” was observed, which was mainly due to the delamination between the dielectric and Si substrate. It was also found that for Si die, “pop-out” was observed without any AE event during the unloading stage, which was related to the Si phase transformation. This observation is unique to sharp indenter tip but not for a blunt indenter tip.